142k views
1 vote
An Accountant using the expressions (4a+3b-6c) and (5a+c) to calculate the total compensation for employees in two different departments of a business.

What is the sum of the two expressions?​

User Ykok
by
5.7k points

1 Answer

4 votes

Answer:

The sum of two expressions will be:


  • \left(4a+3b-6c\right)+\left(5a+c\right)=9a+3b-5c

Explanation:

Given the expressions


  • (4a+3b-6c)

  • (5a+c)

Let us calculate the sum of two expressions


\left(4a+3b-6c\right)+\left(5a+c\right)

Remove the parentheses: (a)=a


=4a+3b-6c+5a+c

Group like terms


=4a+5a+3b-6c+c

Add similar elements: 4a+5a=9a


=9a+3b-6c+c

Add similar elements: -6c+c=-5c


=9a+3b-5c

Thus, the sum of two expressions will be:


  • \left(4a+3b-6c\right)+\left(5a+c\right)=9a+3b-5c
User Pazzo
by
5.3k points